Biocompatible, uniform, and redispersible mesoporous silica nanoparticles for cancer-targeted drug delivery in vivo - Zhang, Quan (2014)
Engineering multifunctional nanocarriers for targeted drug delivery shows promising potentials to revolutionize the cancer chemotherapy. Simple methods to optimize physicochemical characteristics and surface composition of the drug nanocarriers need to be developed in order to tackle major challenges for smooth translation of suitable nanocarriers to clinical applications. Here, rational development and utilization of multifunctional mesoporous silica nanoparticles (MSNPs) for targeting MDA-MB-231 xenograft model breast cancer in vivo are reported. Uniform and redispersible poly(ethylene glycol)-incorporated MSNPs with three different sizes (48, 72, 100 nm) are synthesized. They are then functionalized with amino-β-cyclodextrin bridged by cleavable disulfide bonds, where amino-β-cyclodextrin blocks drugs inside the mesopores. The incorporation of active folate targeting ligand onto 48 nm of multifunctional MSNPs (PEG-MSNPs48-CD-PEG-FA) leads to improved and selective uptake of the nanoparticles into tumor. Targeted drug delivery capability of PEG-MSNPs48-CD-PEG-FA is demonstrated by significant inhibition of the tumor growth in mice treated with doxorubicin-loaded nanoparticles, where doxorubicin is released triggered by intracellular acidic pH and glutathione. Doxorubicin-loaded PEG-MSNPs48-CD-PEG-FA exhibits better in vivo therapeutic efficacy as compared with free doxorubicin and non-targeted nanoparticles. Current study presents successful utilization of multifunctional MSNP-based drug nanocarriers for targeted cancer therapy in vivo.